2022-RA-690-ESGO Unilateral inguinofemoral lymphadenectomy in patients with early-stage vulvar squamous cell carcinoma and a unilateral metastatic sentinel lymph node is safe. (20th October 2022) - Kolk, Willemijn L van der; Zee, Ate GJ van der; Slomovitz, Brian; Baldwin, Peter JW; Doorn, Helena C van; de Hullu, Joanne A; Velden, Jacobus van der; Gaarenstroom, Katja N; Slangen, Brigitte FM; Kjølhede, Preben; Brännström, Mats; Vergrote, Ignace; et al.
Abstract : Introduction/Background: Optimal management of the contralateral groin in patients with early-stage vulvar squamous cell carcinoma (VSCC) and a metastatic unilateral inguinal sentinel lymph node (SN) is unclear. We analyzed patients who participated in GROningen INternational Study on Sentinel nodes in Vulvar cancer (GROINSS-V) I or II to determine whether treatment of the contralateral groin can safely be omitted in patients with a unilateral metastatic SN. Methodology: We selected the patients with a unilateral metastatic SN from the GROINSS-V I and II databases. We determined the incidence of contralateral additional non-SN metastases in patients with unilateral SN-metastasis who underwent bilateral inguinofemoral lymphadenectomy (IFL). In those who underwent only ipsilateral groin treatment or no further treatment, we determined the incidence of contralateral groin recurrences during follow-up. Results: Of 1912 patients with early-stage VSCC, 366 had a unilateral metastatic SN. Subsequently, 244 had an IFL or no treatment of the contralateral groin. In eight patients (8/244; 3.3% [95% CI: 1.7%-6.3%]) disease was diagnosed in the contralateral groin: six had contralateral non-SN metastasis at IFL and two developed an isolated contralateral groin recurrence after nu further treatment. Six of them had a primary tumor ≥30 mm. Bilateral radiotherapy was administered in 122 patients, of whom one (1/122; 0.8% [95% CI: 0.1%-4.5%]) had a contralateral groin recurrence. Conclusion: The risk of contralateral lymph node metastases in patients with early-stage VSCC and a unilateral metastatic SN is low. It appears safe to limit groin treatment to unilateral IFL or inguinofemoral radiotherapy in these cases, particularly if the primary tumor is <30 mm.